Implementation of the Smart Method in Selection of Contraceptive Devices in Couples of Childbearing Age Case Study: Datar City Health Center - Rahmawati; Rusmin Saragih; Mili Alfhi Syari (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
In a marriage, the presence of a child is something that is desired. The Indonesian government, in particular, the National Population and Family Planning Agency (BKKBN) advises husband and wife couples to have a maximum of 2 children. One way to plan the number and timing of pregnancies is to use contraception. This research implements the SMART (Specific, Measurable, Achievable, Relevant, and Time-bound) Method in the selection of contraceptives for couples of reproductive age at the Kota Datar Health Center. The results obtained from the research conducted show that the SMART method used in this system has been proven to be effective in helping select contraceptives for couples of childbearing age in the Datar City Community Health Center case study, because it can select alternatives and carry out rankings in determining the right contraceptive for couples of childbearing age. according to needs based on predetermined criteria, where the injection alternative (A04) with a final score of 83 is a suitable contraceptive for couples of childbearing age according to their needs.